2015
DOI: 10.1007/s10068-015-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Transfer rates of toxic metals during decoction preparation from hebal medicines and safety evaluation of the final decoction products

Abstract: Transfer rates of toxic metals during herbal decoction preparation were investigated using risk assessment tools. Decoction samples were analyzed using Inductively Coupled Plasma-Mass Spectrometer (ICP-MS) and a mercury analyzer after microwave digestion. The average decoction transfer rate (%) for each toxic metal after boiling was 10.5 for As, 4.3 for Pb, 4.1 for Cd, and 2.7 for Hg. A risk assessment of toxic metals in decoctions was performed based on the percentage provisional tolerable weekly intake (PTWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In another work, the following sequence of extraction efficiencies was observed (Cd: 53.1%, Pb: 47.5%, Zn: 39.02%, Mn: 19.98%, Cu: 14.4%, and Fe: 10.09%) [ 26 ]; the results for Cd, Pb, and Mn were in conflict with the results obtained in the present study. However, in agreement with results of the present study, a recent study showed that the extraction efficiencies for Pb and Cd from raw material of herbs to the infusion solutions were 4.3% and 4.1%, respectively [ 31 ]. In another related work, the extraction efficiencies of various metals from ten herbs were reported as Zn: 35%, Cu: 33%, Mn: 24%, and Fe: 6% [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In another work, the following sequence of extraction efficiencies was observed (Cd: 53.1%, Pb: 47.5%, Zn: 39.02%, Mn: 19.98%, Cu: 14.4%, and Fe: 10.09%) [ 26 ]; the results for Cd, Pb, and Mn were in conflict with the results obtained in the present study. However, in agreement with results of the present study, a recent study showed that the extraction efficiencies for Pb and Cd from raw material of herbs to the infusion solutions were 4.3% and 4.1%, respectively [ 31 ]. In another related work, the extraction efficiencies of various metals from ten herbs were reported as Zn: 35%, Cu: 33%, Mn: 24%, and Fe: 6% [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…The quantity of contaminants can be changed in manufacturing process for final products. A study presented the significantly low transfer rates of toxic metals (10.5% for As, 4.1% for Cd, 4.3% for Pb, and 2.7% for Hg) after decoction process of herbal formulae [ 42 ]. One study reported a 5.3% detection rate of residual pesticides and 0.9% excess MRLs rate among 1565 medicinal herbs [ 43 ], and another study presented the 12.5% excess MRLs rate among136 medicinal herbals [ 44 ] in Korea.…”
Section: Discussionmentioning
confidence: 99%